2023
DOI: 10.5937/afmnai40-40667
|View full text |Cite
|
Sign up to set email alerts
|

A correlation between body mass index and refractive errors

Abstract: Background. Body mass index (BMI) is a person's weight in kilograms (or pounds) divided by the square of height in meters (or feet). Obesity affects a wide spectrum of age groups, from the young to the elderly, and there are several eye diseases related to obesity like diabetic retinopathy, floppy eyelid syndrome, retinal vein occlusion, stroke-related vision loss, age-related macular degeneration, and possibly, refractive errors. Refractive errors (RE) are optical imperfections related to the focusing ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
2
2
Order By: Relevance
“…According to Rattan et al study where 400 participants were included during the period of E-Learning, 94.8% of students had refractive errors in AL-Kindy College of Medicine in Iraq. 1 In a cross-sectional study that was conducted among a sample size of 374 medical students at King Abdul-Aziz University Hospital, the prevalence of myopia was 66.7% which is still higher than the current study (40%). It should be noted that the mentioned study was done during COVID pandemic and it was assumed that the frequency of myopia, astigmatism and hyperopia was 66.7%, 35.6%, and 31.1% respectively.¹⁴ Another study conducted on medical students from Al-Jouf region of Saudi Arabia demonstrated that 83.1% were suffering from refractive errors, 74.13% of them were myopic, and 53.73% of them had astigmatism.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…According to Rattan et al study where 400 participants were included during the period of E-Learning, 94.8% of students had refractive errors in AL-Kindy College of Medicine in Iraq. 1 In a cross-sectional study that was conducted among a sample size of 374 medical students at King Abdul-Aziz University Hospital, the prevalence of myopia was 66.7% which is still higher than the current study (40%). It should be noted that the mentioned study was done during COVID pandemic and it was assumed that the frequency of myopia, astigmatism and hyperopia was 66.7%, 35.6%, and 31.1% respectively.¹⁴ Another study conducted on medical students from Al-Jouf region of Saudi Arabia demonstrated that 83.1% were suffering from refractive errors, 74.13% of them were myopic, and 53.73% of them had astigmatism.…”
Section: Discussioncontrasting
confidence: 66%
“…A study in India including 227 students, found myopia in 89.42% and hyperopia in 10.13%.¹⁶ Myopia was consistently found to be the most common refractive error among medical students in other studies as well. 1 ⁷ ˊ1⁸ However, the current study showed lower frequency of myopia as compared to previous studies among medical students. This can be explained by the study parameters as we included myopia and myopic astigmatism as separate groups and there were 18% of the students who did not know the type of refractive error they had.…”
contrasting
confidence: 81%
See 2 more Smart Citations